A replication-incompetent CD154/40L recombinant vaccinia virus induces direct and macrophage-mediated antitumor effects in vitro and in vivo. (4th May 2019) - Governa, Valeria; Brittoli, Alvaro; Mele, Valentina; Pinamonti, Maurizio; Terracciano, Luigi; Muenst, Simone; Iezzi, Giandomenica; Spagnoli, Giulio Cesare; Zajac, Paul; Trella, Emanuele
ABSTRACT: CD40 triggering may result in antitumor effects of potentially high clinical relevance. To gain insights important for patient selection and to identify adequate targeting techniques, we investigated CD40 expression in human cancer tissues and generated a replication-incompetent recombinant vaccinia virus expressing CD40 ligand (rVV40L). Its effects were explored in vitro and in vivo upon direct CD40 targeting on malignant cells or macrophage activation. CD40 expression was analyzed by immunohistochemistry in tumor and stromal cells in a multi-tumor array including 836 specimens from 27 different tumor types. Established tumor cell lines were used to explore the capacity of rVV40L to induce malignant cell apoptosis and modulate functional profiles of polarized macrophages. CD40 expression was detectable in significantly higher numbers of stromal as compared to malignant cells in lung and breast cancers. CD40 ligation following rVV40L infection induced apoptosis in CD40(+) cancer cells, but only in the presence of intact specific signal transduction chain. Importantly, rVV40L infection promoted the induction of TNF-α-dependent antitumor activity of M1-like macrophages directed against CD40(-) targets. CD40-activated M1-like macrophages also displayed enhanced ability to CXCL10-dependently recruit CD8+ T cells and to efficiently present cancer cell intracellular antigens through cross-priming. Moreover, rVV-driven CD40L expression partially "re-educated" M2-like macrophages, as suggested by detectable CXCL10 and IL-12 production. Most importantly, we observed that intra-tumoral injection of rVV40L-infected human macrophages inhibits progression of human CD40(-) tumors in vivo . First evidences of anticancer activity of rVV40L strongly encourage further evaluations.